Communication Strategies for Micro, Small, and Medium Enterprises Participation in The Sagarurung Festival, Pali Regency - Meisya Anggraini; Esxi Martia Gusma; Bimo Kuncoro Jati; Raty Rusmiana (Tulisan Ilmiah Pariwisata (TULIP), 2026)
This study aims to analyze communication strategies implemented to enhance Micro, Small, and Medium Enterprises (MSMEs) participation in the Sagarurung Festival in PALI Regency. MSMEs play a significant role in supporting regional economic development, particularly through tourism-based events and creative economy activities. This research applies a qualitative research approach by utilizing in-depth interviews, direct observation, document analysis, and SWOT analysis supported by IFAS and EFAS frameworks. Informants were selected using purposive sampling, involving representatives from the Office of Cooperatives and SMEs of PALI Regency, festival organizers, and MSME participants. Data were analyzed using the interactive model of Miles and Huberman. The findings indicate that the communication strategy implemented in the Sagarurung Festival reflects an Integrated Marketing Communication (IMC) approach, incorporating advertising, sales promotion, public relations, personal selling, and direct and digital marketing. Digital communication and interpersonal communication emerged as the most effective strategies in facilitating MSME participation. WhatsApp and social media became the primary communication channels due to their accessibility, speed, interactivity, and efficiency. Furthermore, free booth facilities reduced participation barriers, while public relations and interpersonal communication strengthened trust and sustainable relationships between organizers and MSMEs.